GLP-1 receptor agonists in diabetic kidney disease: current evidence and future directions - Ji Hee Yu; So Young Park; Da Young Lee; Nan Hee Kim; Ji A Seo (The Korean Society of Nephrology, 2022)
With the emergence of various classes of blood glucose-lowering agents, choosing the appropriate drug for each patient is emphasized in diabetes management. Among incretin-based drugs, glucagon-like peptide 1 (GLP-1) receptor agonists are a promising therapeutic option for patients with diabetic kidney disease (DKD). Several cardiovascular outcome trials have demonstrated that GLP-1 receptor agonists have beneficial effects on cardiorenal outcomes beyond their blood glucose-lowering effects in patients with type 2 diabetes mellitus (T2DM). The renal protective effects of GLP-1 receptor agonists likely result from their direct actions on the kidney, in addition to their indirect actions that improve conventional risk factors for DKD, such as reducing blood glucose levels, blood pressure, and body weight. Inhibition of oxidative stress and inflammation and induction of natriuresis are major renoprotective mechanisms of GLP-1 analogues. Early evidence from the development of dual and triple combination agents suggests that GLP-1 receptor agonists will probably become popular treatment options for patients with T2DM.